Community Science for Coastal Acidification Monitoring and Research. Issue 5 (26th June 2021) - Gassett, Parker Randall; O'Brien-Clayton, Katie; Bastidas, Carolina; Rheuban, Jennie E.; Hunt, Christopher, W.; Turner, Elizabeth; Liebman, Matthew; Silva, Emily; Pimenta, Adam, R.; Grear, Jason.; Motyka, Jackie; McCorkle, Daniel; et al.
Abstract: Ocean and coastal acidification (OCA) present a unique set of sustainability challenges at the human-ecological interface. Extensive biogeochemical monitoring that can assess local acidification conditions, distinguish multiple drivers of changing carbonate chemistry, and ultimately inform local and regional response strategies is necessary for successful adaptation to OCA. However, the sampling frequency and cost-prohibitive scientific equipment needed to monitor OCA are barriers to implementing the widespread monitoring of dynamic coastal conditions. Here, we demonstrate through a case study that existing community-based water monitoring initiatives can help address these challenges and contribute to OCA science. We document how iterative, sequential outreach, workshop-based training, and coordinated monitoring activities through the Northeast Coastal Acidification Network (a) assessed the capacity of northeastern United States community science programs and (b) engaged community science programs productively with OCA monitoring efforts. Our results (along with the companion manuscript) indicate that community science programs are capable of collecting robust scientific information pertinent to OCA and are positioned to monitor in locations that would critically expand the coverage of current OCA research. Furthermore, engaging community stakeholders in OCA science and outreach enabled a platform for dialogue about OCA among other interrelated environmental concerns and fostered a series of co-benefits relating to public participation in resource and risk management. Activities in support of community science monitoring have an impact not only by increasing local understanding of OCA but also by promoting public education and community participation in potential adaptation measures.